Estrus synchronization of replacement beef heifers by using GnRH, prostaglandin F2α (PGF), and progesterone (CIDR): a multi-location study - Larson, J.E.; Lamb, G.C.; Geary, T.W.; Stevenson, Jeffrey S.; Johnson, Sandra K.; Day, M.L.; Kesler, D.J.; DeJarnette, J.M.; Landblom, D.G.; Whittier, D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our objectives were to determine whether a fixed-timed artificial insemination (TAI) protocol could yield similar fertility rates to a protocol requiring detection of estrus and whether an injection of gonadotropin hormone-releasing hormone (GnRH) at CIDR (vaginal insert containing progesterone) insertion enhances pregnancy rates. Replacement beef heifers (n=2,077) from 12 locations were assigned randomly to each of four estrussynchronization protocols. All heifers received a CIDR for 7 days, and an injection of prostaglandin F2α (PGF) on the day of CIDR removal. For treatment EAI, heifers were observed for estrus for 84 hours after PGF administration and were inseminated 6 to 12 hours after observed estrus. Any heifer not detected in estrus was injected with GnRH, followed by TAI. For treatment GnRH+EAI, heifers were treated as those for EAI, but also received GnRH at the time of CIDR insertion. For treatment TAI, heifers received a single TAI at 60 hours after PGF administration. For treatment GnRH+TAI, heifers were treated as those for TAI, but also received GnRH at CIDR insertion. The percentage of heifers cycling at the initiation of estrus-synchronization was 91%; the percentage of cycling heifers among locations ranged from 78 to 100%. Overall pregnancy rates among locations ranged from 38 to 74%. Pregnancy rates were 57.3, 54.5, 53.1, and 49.1% for GnRH+EAI, EAI, GnRH+TAI, and TAI, respectively. Although no statistically significant differences in pregnancy rates among treatments were observed, the GnRH+EAI treatment achieved the numerically greatest pregnancy rates. In addition, the GnRH+TAI protocol provides an alternative that allows producers to synchronize heifers without detection of estrus.
Keywords: Beef; Estrus synchronization; GnRH; Prostaglandin F2α (PGF); Progesterone (CIDR)